Bacterial populations and the volatilome associated to meat spoilage. (February 2015) - Casaburi, Annalisa; Piombino, Paola; Nychas, George-John; Villani, Francesco; Ercolini, Danilo
Abstract: Microbial spoilage of meat is a complex event to which many different bacterial populations can contribute depending on the temperature of storage and packaging conditions. The spoilage can derive from microbial development and consumption of meat nutrients by bacteria with a consequent release of undesired metabolites. The volatile organic compounds (VOCs) that are generated during meat storage can have an olfactory impact and can lead to rejection of the product when their concentration increase significantly as a result of microbial development. The VOCs most commonly identified in meat during storage include alcohols, aldehydes, ketones, fatty acids, esters and sulfur compounds. In this review, the VOCs found in fresh meat during storage in specific conditions are described together with the possible bacterial populations responsible of their production. In addition, on the basis of the data available in the literature, the sensory impact of the VOCs and their dynamics during storage is discussed to highlight their possible contribution to the spoilage of meat. Highlights: Many volatile organic compounds can be produced in meat by spoilage microorganisms. The type of storage affects number and type of spoilage molecules. VOCs are potential odor-active markers of microbiological spoilage in meat. Volatile fatty acids and ketones contribute with fatty, gamy, cheesy and dairy notes. Alcohols and esters contribute with their ethereal, fruity and sweet notes.